If A + B + C = 180°, Prove that

Sin² (A/2) + sin² (B/2) - sin²(C/2) = 1 – 2cos (A/2) cos (B/2) sin(C/2)

Similar Questions
  1. If A + B + C = 180°, Prove thatSin² (A/2) + sin² (B/2) + sin²(C/2) = 1 – 2sin (A/2) sin (B/2) sin(C/2)
    1. answers icon 0 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. What is the first step. Explain please.Which expression is equivalent to cos^2x + cot^2x + sin2^x? a) 2csc^2x b) tan^2x c)
    1. answers icon 4 answers
more similar questions